Toward highly effective loading of DNA in hydrogels for high-density and long-term information storage - Fei, Zhongjie (2023)
Digital information, when converted into a DNA sequence, provides dense, stable, energy-efficient, and sustainable data storage. The most stable method for encapsulating DNA has been in an inorganic matrix of silica, iron oxide, or both, but are limited by low DNA uptake and complex recovery techniques. This study investigated a rationally designed thermally responsive functionally graded (TRFG) hydrogel as a simple and cost-effective method for storing DNA. The TRFG hydrogel shows high DNA uptake, long-term protection, and reusability due to nondestructive DNA extraction. The high loading capacity was achieved by directly absorbing DNA from the solution, which is then retained because of its interaction with a hyperbranched cationic polymer loaded into a negatively charged hydrogel matrix used as a support and because of its thermoresponsive nature, which allows DNA concentration within the hydrogel through multiple swelling/deswelling cycles. We were able to achieve a high DNA data density of 7.0 × 109 gigabytes per gram using a hydrogel-based system.